A Lexicon of Medieval Nordic Law - Love, Jeffrey (Open Book Publishers, 2020)
"This volume is an indispensable resource for scholars and students of medieval Scandinavia. This polyglot dictionary draws on the vast and vibrant range of vernacular legal terminology found in medieval Scandinavian texts - terminology which yields valuable insights into the quotidian realities of crime and retribution; the processes, application and execution of laws; and the cultural and societal concerns underlying the development and promulgation of such laws. Legal texts constitute an unparalleled - and often untapped - source of information for those studying the literature, languages and history of medieval and Viking Age Scandinavia. The Lexicon is a welcome contribution to the study of medieval Scandinavia on two counts: firstly, it makes accessible a wealth of vernacular historical documents for an English-speaking audience. Secondly, it presents legal terminologies that span the languages and geographies of medieval Scandinavia, drawing on twenty-five legal texts composed in Old Swedish, Old Icelandic, Old Norwegian, Old Danish, Old Gutnish and Old Faroese. By collating and juxtaposing legal terms, the Lexicon thus offers its readers a fascinating, comprehensive window into the legal milieu of medieval Scandinavia as a unified whole. It is in this respect that A Lexicon of Medieval Nordic Law differs from the other major lexica that came before it: where relevant, it gathers closely related terms from multiple Nordic languages beneath single headwords within single entries. This approach illuminates the differences (and similarities) in usage of specific lexical items and legal concepts across geographic areas and through time. This dictionary contains over 6000 Nordic headwords, and is laid out as a standard reference work. It is easily navigable, with a clear structure to each entry, providing English equivalents; textual references; phrases in which headwords frequently appear; cross-references to aid readers in locating synonyms or cognate terms within the lexicon; and references to published works. Roughly one quarter of the headwords supply semantic analysis and detailed information on the textual and historical contexts within which a term might appear, which help the reader to engage with the broader legal concepts underlying specific terms. The Lexicon is thus designed to provide its readers not only with succinct single definitions of Norse legal terms, but with a sense of the wider Scandinavian legal landscape and worldview within which these concepts were developed."